Collenchyma in Panicum maximum (Poaceae): localisation and possible role - Paiva, EAS; Machado, SR (CSIRO Publishing, 2003)
This work relates the occurrence and distribution of collenchyma in Panicum maximum Jacq. P. maximum leaves were collected at different phases of development and sampled from both the base of the sheath and from the sheath-leaf blade transition area. For the stems, the study was made by using hand-cut sections of the internodal base. In the leaves, analyses of serial sections showed, at the base and sheath-leaf blade transition area, a sudden change of tissue at vascular bundle. The vascular bundles are surrounded by sclerenchyma, both in the sheath and the leaf blade, as well as by fibrous threads that occur on the adaxial side of the central bundles. However, at the base of the sheath and at the sheath-leaf blade transition area, sclerenchyma was substituted for collenchyma. In the stem, the substitution of sclerenchyma associated with vascular bundles for collenchyma occurs at the base of the internode, in the pulvinus region. The analyses from transmission electron microscopy showed the presence of lamellated cell wall and active protoplast in collenchyma cells.